Analisis Inovasi Produk Dan Kualitas Produk Terhadap Keunggulan Bersaing Pada Kerajinan Rotan Di Kota Medan - Dian Septiana Sari (Forum Kerjasama Pendidikan Tinggi, 2022)
The research analysis aims to determine whether product innovation and product quality partially and simultaneously have a positive and significant effect on the competitive advantage of rattan craftsmen in Jalan Gatot Subroto, Medan City. The data analysis technique used is the quantitative method with the help of the SPSS version 26.0 program. This study uses multiple linear regression analysis. The sample in this study was 77 respondents. Primary data collection using a questionnaire. The results showed that the effect of product innovation on competitive advantage was seen that count 4.282 > table 1.664 and significant 0.000 <0.05. The effect of product quality on competitive advantage is seen in that count 3.190 > table 1.664 and significant 0.002 <0.05. The effect of Product Innovation and Product Quality together (simultaneously) has a positive effect on Competitive Advantage (Fount> Ftable 34.602 > 2.72 at significant 0.000 <0.05).